2021
DOI: 10.3390/cancers13071559
|View full text |Cite
|
Sign up to set email alerts
|

Which Is the Best Treatment in Recurrent Thymoma? A Systematic Review and Meta-Analysis

Abstract: Background: Optimal recurrent thymoma management remains arguable because of limited patient numbers, and relatively late and variable recurrence patterns. Given the absence of high-quality evidence and relatively small study cohorts, we performed a quantitative meta-analysis to determine the outcome of surgical and non-surgical approaches assessing the five-year overall survival (5y overall survival (OS)) in patients with recurrent thymoma. Methods: We performed a comprehensive literature search and analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Regarding meta-analyses, Hamaji et al analysed 11 studies and reported favourable 5-year overall survival of re-resected cases after thymoma recurrence [ 19 ]. Chiappetta et al analysed 7 studies, including our initial report from JART, and concluded that re-resection was associated with better 5-year overall survival, which should be preferred [ 20 ]. In addition to re-resection, limited number of studies discuss the experiences and outcomes of hyperthermic intrathoracic chemotherapy for disseminated thymoma [ 21–24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding meta-analyses, Hamaji et al analysed 11 studies and reported favourable 5-year overall survival of re-resected cases after thymoma recurrence [ 19 ]. Chiappetta et al analysed 7 studies, including our initial report from JART, and concluded that re-resection was associated with better 5-year overall survival, which should be preferred [ 20 ]. In addition to re-resection, limited number of studies discuss the experiences and outcomes of hyperthermic intrathoracic chemotherapy for disseminated thymoma [ 21–24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this patient, the location of the recurrent thymoma posed a great surgical risk and reoperation was abandoned. 1 The IL-23/ Th17 pathway in myasthenia gravis relating to thymoma was active 2 ; therefore the patient was given a combination treatment of radiotherapy (total of 60 Gy in 28 fractioned doses) for the recurrent thymoma and subcutaneous injection of ixekizumab. After 2 months of presentation, the patient's skin symptoms were greatly improved.…”
Section: Microscopic Findings and Clinical Coursementioning
confidence: 99%
“…The definition of advanced thymoma is based on pathological specimens presenting infiltration of thoracic structures, such as mediastinal pleura, pericardium, phrenic nerve, lungs, large vessels, etc.) or pleural-pericardial spread [ 22 ]. The subxiphoid VATS approach may also be appropriate for treating some locally advanced thymic tumors [ 48 ].…”
Section: Surgical Treatment For Thymic Tumormentioning
confidence: 99%
“…Surgical resection is the mainstay of the treatment for thymoma and thymic carcinoma, while a multimodal approach is proved to be useful for many patients [ 7 , 20 , 21 , 22 ]. The ability to perform complete surgical resection to treat thymic carcinoma and thymoma is an important factor in recurrence and survival after surgery [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%